ANALISIS FAKTOR LINGKUNGAN TERHADAP DISTRIBUSI JENIS TIKUS YANG TERKONFIRMASI SEBAGAI RESERVOIR LEPTOSPIROSIS DI TIGA KABUPATEN DI PROVINSI SUMATERA SELATAN - Yanelza Supranelfy; Nungki Hapsari S; Reni Oktarina (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2019)
The role of rats as a potential reservoir of the disease remains negative impacts on the routine life, safety, welfare and economic communities. Rattus tanezumi, R. norvegicus, R. exulans, R. hoffmani, R. argentiventer and Maxomys bartelsi have been confirmed as leptospirosis reservoirs in Indonesia. Some rat species suspected as leptospirosis reservoirs were reported in Lahat, Banyuasin and Ogan Komering Ilir (OKI) districts. It puts those three districts on high risk of leptospirosis transmission in the community. The aim of the study was to identify the environmental factors associated with the distribution of the leptospirosis-confirmed rats in the three districts of South Sumatera Province. Data used in this study were obtained from surveillance of the Specific Research on Vector and Reservoir Diseases Special Research" (Rikhus Vektora) conducted in 2015. A total of 308 captured rats was tested for leptospirosis using MAT and PCR methods. The environmental variables were recorded during the surveillance. Data were analysed using chi-square. The laboratory results demonstrated that 44 of 308 rats captured in the three districts were positive for leptospirosis. In addition, there was a significant correlation between the distribution of the positive leptospirosis-confirmed rats with ecosystem variables, trap location, altitudes and temperature. However, they were not correlated to the weather variables and pH. Unfortunately, the topographic variables could not be analysed because all rats were found in the lowlands. The early warning of leptospirosis transmission should be addressed to the three districts due to the presence of the positive leptospirosis-confirmed rats in those areas.